Tax Cuts or Direct Transfers? - Gisela Färber (Wirtschaftsdienst)
Abstract The article discusses financial aid and tax exemptions as means to fight against the economic distortions of the current energy crisis. Recent experiences have included not only general stabilisation instruments but also those compensating energy price increases for low-income households and preventing unemployment by helping companies to maintain their workforce during the crisis. The article discusses the efficiency, administrative burden and intergovernmental financial relations of the instruments.